STUDI PEMANFAATAN AIR TANAH DAN POTENSI INTRUSI AIR LAUT DI DAERAH PESISIR KOTA BALIKPAPAN - Septiardi, Muhammad Evan; Mislan, Mislan; Natalisanto, Adrianus Inu (GEOSAINS KUTAI BASIN, 2019)
Research on the quality of ground water has been performed through boreholes in the city of Balikpapan to find out an indications of the potential of sea water intrusion based on data. The study began with choosing the companies as groundwater user in two places, namely the coastal of manggar and the coastal of the city of Balikpapan. The next steps were to take the drill water samples and examine the quality. The examined were salinity, TDS (Total Dissolve Solid), conductivity and pH of water. The water categories were divided into 3 ie fresh water, with salinity value <1 ppt; brackish with salinity value between 1-3 ppt; and salt water with value> 3 ppt. After those steps the data were interpreted and then contructed to be the image of salinity contour.